Pendampingan Lansia Di Posyandu Lansia Puskesmas Wajak Kecamatan Wajak Kabupaten Malang - Rakhmad Rosadi; Azhar Ihza Pamedar Sabda; Sri Sunaringsih Ika Wardojo (Lembaga Pengembangan Kinerja Dosen, 2023)
Community service was carried out at the Wajak Public Health Center Elderly Posyandu with several activities including providing Anxiety Questionnaires (DASS) and providing education on music therapy and murrotal. With a total of 19 elderly people consisting (5 men and 14 women) of this method using the Anxiety Questionnaire (DASS) to determine the level of anxiety in the elderly. The results are experiencing normal anxiety levels with 13 (68.4%), for mild anxiety levels 8 (31.5%) Counseling runs smoothly, and as knowledge material for the elderly, especially anxiety conditions by providing music and murottal therapy education aimed at increasing relaxation, resting the body , and thoughts, increase motivation, self-development, improve memory and mental health.